Impact of English Movie Subtitles in Increasing English Vocabulary at Higher Secondary School Level - Neeha Noor; Dr. Imran Latif Saifi (Indus Journal of Social Sciences, 2025)
The analysis studies how English animated movie subtitles affect higher secondary school students' vocabulary growth in Pakistan. The study investigates Pakistan's education system because its traditional teaching methods still prevail despite failing to provide both learner engagement and effective vocabulary development strategies. An experimental research at Alpina School & College Bahawalpur examined the alternative approach by splitting forty students into experimental and control groups. Thirty students in the experimental group watched three English animated movies—Wreck-It Ralph, How to Train Your Dragon, and Epic—while following subtitles integrated into lesson plans specifically designed for the project. Both experimental and control groups received vocabulary evaluation through pre-tests and post-tests. Research outcomes showed that students who learned with subtitled videos improved their vocabulary significantly and exhibited stronger motivational drive when compared to classroom-only teaching methods. This research demonstrates using multimedia with subtitles helps English learning education and recommends additional studies to develop innovative teaching methods which improve results for Pakistani students.